Serum S100P and C4d proteins as markers for active proliferative lupus nephritis in Egyptian patients with systemic lupus erythematosus - Mahmoud M. Elnokeety; Noha Khalil; Ahmed Fayed (Український Журнал Нефрології та Діалізу, 2023)
Lupus nephritis (LN), occurring in approximately 50% of individuals with systemic lupus erythematosus (SLE), significantly influences therapy and prognosis. Proliferative LN, more prevalent than non-proliferative LN, is associated with a poorer prognosis. This study aimed to investigate the potential correlation between serum levels of the pro-inflammatory proteins human calcium-binding S100P (S100P) and Human complement Fragment 4 (C4d) and confirmed proliferative LN through biopsy. The objective was to evaluate their reliability as biomarkers for disease activity in proliferative LN.